2009
DOI: 10.1007/s12065-009-0020-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on diversity for cluster geometry optimization

Abstract: Diversity is a key issue to consider when designing evolutionary approaches for difficult optimization problems. In this paper, we address the development of an effective hybrid algorithm for cluster geometry optimization. The proposed approach combines a steady-state evolutionary algorithm and a straightforward local method that uses derivative information to guide search into the nearest local optimum. The optimization method incorporates a mechanism to ensure that the diversity of the population does not dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 45 publications
3
78
0
Order By: Relevance
“…More specifically we selected the instances with the following number of atoms N= {30, 38, 47, 61, 68}. This set includes examples that are considered to be difficult to optimize (see, e.g., (Grosso et al, 2007;Pereira & Marques, 2009)). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…More specifically we selected the instances with the following number of atoms N= {30, 38, 47, 61, 68}. This set includes examples that are considered to be difficult to optimize (see, e.g., (Grosso et al, 2007;Pereira & Marques, 2009)). …”
Section: Resultsmentioning
confidence: 99%
“…In this work we rely on the center of mass distance, a measure that is based on the distance of atoms to the cluster's center of mass (Grosso et al, 2007). Results reported in (Grosso et al, 2007;Pereira & Marques, 2009) confirm that it is effective in accessing the similarity of possible solutions for Morse instances. In general terms, a descendant D is allowed to enter the population if one of the following conditions is satisfied (consult (Lee et al, 2003) for a detailed description of the replacement strategy): i) D is similar to a solution X that belongs to the current population and D is better than X.…”
Section: Evolutionary Algorithmmentioning
confidence: 94%
See 2 more Smart Citations
“…They also suggested that the enhanced results were in most part the outcome of the increased diversity caused by the adaption of the settings. Later Pereira et al [61] introduced an unbiased hybrid steady-state EA combined with a single phase local optimization method based on a general quasi-Newton method. This study includes mechanisms designed to ensure the maintenance of diversity and demonstrates that its preservation is a key point to efficiently tackle CGO problems.…”
Section: Introductionmentioning
confidence: 99%